Design of Dipole Antenna at 433 Mhz ISM Band for Underwater to Land Communication - Erna Alimudin; Arif Sumardiono; Riyani Prima Dewi; Saepul Rahmat; Hendi Purnata; Novita Asma Ilahi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2024)
In this research has been designed dipole antenna which is intended for communication underwater to land that worked and implemented into prototype form. Design using the software Ansoft High Frequency Structural Simulator (HFSS) v13 and analyze parameters which are generated in simulation results, namely the Voltage Standing Wave Ratio (VSWR), reflection coefficient (S11), the radiation pattern of two-dimensional and three-dimensional. On its design was made of two dipole antennas that can work in a system as a transmitter and receiver. Both of these Dipole antenna operating at ISM 433 MHz frequency band and produce VSWR = 1.62 at the transmitter antenna and = 1.406 on the receiving antenna. In addition, has been measured radiation patterns by antenna performance. From the results of radiation patterns measurements, obtained two pieces of Main Lobe in its field azimuth.